The trypomastigote small surface antigen from Trypanosoma cruzi improves treatment evaluation and diagnosis in pediatric chagas disease - Balouz, Virginia (2017)
Chagas disease is caused by the protozoan parasite Trypanosoma cruzi. Assessment of parasitological cure upon treatment with available drugs relies on achieving consistent negative results in conventional parasitological and serological tests, which may take years to assess. Here, we evaluated the use of a recombinant T. cruzi antigen termed trypomastigote small surface antigen (TSSA) as an early serological marker of drug efficacy in T. cruzi-infected children. A cohort of 78 pediatric patients born to T. cruzi-infected mothers was included in this study. Only 39 of the children were infected with T. cruzi, and they were immediately treated with trypanocidal drugs. Serological responses against TSSA were evaluated in infected and noninfected populations during the follow-up period using an in-house enzymelinked immunosorbent assay (ELISA) and compared to conventional serological methods. Anti-TSSA antibody titers decreased significantly faster than anti-whole parasite antibodies detected by conventional serology both in T. cruzi-infected patients undergoing effective treatment and in those not infected. The differential kinetics allowed a significant reduction in the required follow-up periods to evaluate therapeutic responses or to rule out maternal-fetal transmission. Finally, we present the case of a congenitally infected patient with an atypical course in whom TSSA provided an early marker for T. cruzi infection. In conclusion, we showed that TSSA was efficacious both for rapid assessment of treatment efficiency and for early negative diagnosis in infants at risk of congenital T. cruzi infection. Based upon these findings we propose the inclusion of TSSA for refining the posttherapeutic cure criterion and other diagnostic needs in pediatric Chagas disease.